A customized adherence enhancement program combined with long-acting injectable antipsychotic medication (CAE-L) for poorly adherent patients with chronic psychotic disorder in Tanzania: A pilot study methodological report. Issue 6 (June 2019) - Mbwambo, Jessie; Kaaya, Sylvia; Lema, Isaac; Blixen, Carol; Cassidy, Kristin A.; Levin, Jennifer B.; Sajatovic, Martha
Abstract: Chronic psychotic disorders (CPDs) occur worldwide and cause significant burden including reduced quality of life and functional impairment. Care for CPD includes psychosocial and pharmacologic interventions (i.e. antipsychotic drugs) and ongoing health monitoring. This is challenging in resource-limited settings where staff are sparse and/or undertrained. Importantly, mental health human resource needs predict continued deficits compounded by increasing disease burden. A U.S. team recently developed and tested a CPD treatment approach that combines the use of long-acting antipsychotic medication (LAI) with a brief and practical customized adherence enhancement behavioral intervention (CAE-L). This report describes the methodological details of an ongoing, first-ever refinement and preliminary testing of CAE-L in poorly adherent patients with CPD in Tanzania. Additional innovative elements include: 1) a manualized curriculum that targets specific barriers and facilitators to medication adherence in Tanzanians with CPD, and 2) targeting known, high-risk individuals with CPD (those who miss ≥20% of prescribed antipsychotic medication). The study procedures are intended to pave the way for implementing a large-scale intervention trial for CPD in the Tanzanian setting. An important component of this project is capacity building to help form the next generation of care providers. Visit exchanges modeled on a successful NIH-funded Medical Education Partnership Initiative (MEPI) template will also use the U.S. and Tanzanian teams to share expertise, problem-solve, and plan iterative refinements of project deliverables. Taken together, this project has potential to advance the care of people with CPD in Tanzania and has high generalizability to Sub-Saharan Africa and other lower-resource settings.